Cardiac glycosides, phenolic compounds and antioxidant activity from plant cell suspension cultures of Thevetia peruviana (2017)
ABSTRACT: Cell suspension cultures of Thevetia peruviana were established under dark for 19 days to investigate kinetic behavior related to biomass, substrate, cardiac glycoside, polyphenols, reactive oxygen species and anti-oxidant activity. The results showed high biomass production (18.80gDW/L) as well as sucrose consumption in 7 days. Preferential glucose over fructose consumption was observed. Intracellular production of cardiac glycosides reached 2.58mg DE/gDW at day 19. Highest extracellular production was reached between day 2 and 7 (6.19mg DE/L). Highest extracellular phenolic content was 80.61 ± 5.16mg GAE/L at day 7. Intracellular phenolic content increased to 2.76 ± 0.14mg GAE/gFW at day 7 and remained constant until day 19. ROS production at day 7 could be related to sucrose and glucose total consumption. Pearson Product-Moment Correlation Coefficient (ρ) showed that the phenolic compounds in cell suspension cultures of T. peruviana were responsible for the observed anti-oxidant activity. All together, these results give the first steps in metabolic behavior in cell suspension cultures of T. peruviana.